Global, Regional, and National Estimates and Trends in Stillbirths From 2000 to 2019: A Systematic Assessment. Issue 2 (February 2022) - Hug, Lucia; You, Danzhen; Blencowe, Hannah; Mishra, Anu; Wang, Zhengfan; Fix, Miranda J.; Wakefield, Jon; Moran, Allisyn C.; Gaigbe-Togbe, Victor; Suzuki, Emi; Blau, Dianna M.; Cousens, Simon; et al.
Abstract : (Abstracted from Lancet 2021 ;398:772–785) Stillbirths are a public health issue as well as an example of the inequality of care during pregnancy and birth. Groups such as the UN Global Strategy for Women's, Children's, and Adolescents' Health and the Every Newborn Action Plan aim to prevent stillbirths.